Implementasi Keamanan pada Transaksi Data Menggunakan Sertifikat Digital X.509 - Is Mardianto; Kuswandi Kuswandi (Ultimatics : Jurnal Teknik Informatika, 2016)
Security issues have become a major issue on the Internet. One of the security methods that are widely used today is to implement a digital certificate. Digital certificates have evolved over time, one of which is the X.509 digital certificate. Digital certificates have been widely used as authentication applications, web network authentication and other authentication systems that require digital certificates. This research is carried out by implementing an X.509 digital certificate technology as a mobile web service with its client. Secure Hash Algorithm (SHA), Diffie-Hellman, and Advanced Encryption Standard (AES) are used to secure the data exchange transaction between the web service and mobile phone. SHA algorithm will be used for user authentication, Diffie-Hellman algorithm will be used for public key exchange and AES algorithms will be used for symmetric cryptography data. The results of the application of digital certificates, the SHA algorithm, Diffie-Hellman, and AES in mobile phone applications, provide security application running on web service. Index Terms—Digital Certificate, X.509, SHA, Diffie Hellman, AES